Distributional effects of higher cassava yields in Nigeria: An ex ante analysis - Minot, Nicholas; Huang, Rachel (International Food Policy Research Institute, 2019)
This study demonstrates a method of providing ex-ante estimates of the distributional welfare effects of yield-increasing technology. We apply this approach to estimate the impact of a 10% increase in cassava yields in Nigeria. Using data from the 2012-13 Nigeria General Household Survey, we simulate the effect of the technology on each household in the sample (micro-simulation), taking into account both the yield increase and the resulting price reduction. The results suggest that the higher cassava yield would increase average household income by 0.2 percent, generate aggregate benefits of US$ 219 million per year, and reduce poverty by 0.2 percentage points, lifting 385 thousand people from poverty. Cassava growers who have net sales (11 percent of Nigerian households) would experience a reduction in income and an uptick in poverty due to the lower price. However, net-buying growers (10 percent) and consumers (47 percent) would benefit both in terms of income and poverty reduction. Smaller farms gain since many are net buyers who benefit from the lower price. Larger farms lose because many of them are net sellers who are adversely affected by the lower price. As most of the benefits of technology change are transferred to consumers (including many rural consumers), the cassava consumption patterns are at least as important as grower characteristics in determining the distributional impact of the technology. Applying this approach to all major crops in a country would help policy makers prioritize agricultural research across commodities to increase the poverty-reducing impact.